Aplicação da técnica recozimento simulado (simulated annealing) para otimização de reservatórios de pequenas centrais hidrelétricas em cascata - Stelle, Charleston (2015)
The Brazil`s growing demand for electricity led to the exploration of alternative sources in the early 2000s, making possible through flexible business rules and systemic development of Small Hydro Power Plants (SHPP). After nearly two decades, new regulations were needed to regulate the SHPP market, given the records of low efficiency displayed throughout the operation of these plants, increasing the impact on the Electricity Brazilian Market. Somehow, this work presents one overview of the main regulatory frameworks for this type of generation source, beyond current market rules, which is remarkable the need to develop tools that enable the optimal and efficient operation rules for operation this kind of power plants, to avoid regulatory penalties. This paper presents the application of a metaheuristic, called Simulated Annealing, used for dispatch optimization of power generation regarding two small hydropower plants in cascade, in order to achieve optimal daily regulation, and seek the optimal operating point and taking advantage the potential of each reservoir so it is expected that the total generation cascade were maximized. The optimization technique is applied to an objective function, which represents the mathematical model of daily dispatch for two small hydropower plants, observing the individual operating technical restrictions, its considering a short-term planning horizon, i.e, for five days of operation. The results of the computer model were satisfactory when compared with the data recorded in the generation of small hydropower plants.